STEM for Establishing Energy Literacy in Maritime Vocational Education - Iing Mustain; Yeyen Herlina (Tadris Biologi Fakultas Ilmu Tarbiyah dan Keguruan IAIN SYEKH NURJATI CIREBON, 2019)
The development of new and renewable energy is an essential issue in the 21st century that must be delivered to the community, and maritime vocational education has an urgency on the energy literacy for ship engineering cadets. However, learning about energy for engineering cadets still lacks attention. The purpose of this paper is to describe energy literacy, which is reviewed based on the cognitive and affective aspects of cadets in maritime vocational education. This research used the quasi-experiment method, which a total of 61 engineering cadets learned about energy use using the STEM approach. From the results was found that although the achievement of understanding energy literacy from pre-test to post-test score with a small increase but the attitude of cadets towards the importance energy education has 76%, energy-saving attitude on ships 71%, the use of renewable energy 68%, rules on energy use according to ANNEX it must be obeyed is 71%. These results illustrate that it is necessary to continue and add of learning time to increase the cognitive aspects of energy literacy and to improve awareness of the cadets' attitudes about the importance of saving energy and its utilization.